Advertising Effectiveness In Events - Jain, Sushilkumar (2012)
Confronted with decreasing effectiveness of the classic marketing communications, events have become an increasingly popular alternative for marketers. Events constitute one of the most exciting and fastest growing forms of leisure and business. With time, the decreasing effectiveness of classical marketing communications boosted the use of events for marketing and making brand awareness. Event marketing is seen as the unique opportunity to integrate the firm’s communication activities like public relations, advertising, and direct marketing, in a sense which enables consumers to interact with brands. The basic objective of any industry is to deliver the product in market with making profits and merchandising. This can be done with the help increase in sales at remunerative prices. Advertising is the major player for reach of products and services to the consumers and a varied method of publicity. American Marketing Association (2006) defines advertising as “any paid form of non personal presentation and promotion of ideas, goods and/or services by identified sponsor” (Kotler and Keller, 2009). This particular researcher paper focuses on the advertising effectiveness in (sports) events, London Olympic Games 2012. The focus of particular research is to gather knowledge from attendee’s about the sponsors advertisements and products. Research work entails on understanding the effectiveness of advertisements by sponsors for promoting and maintaining brand image in public. Study conducts 40 semi-structured interviews to understand the aspects of advertising effectiveness, and also explore the emotional and cognitive effects that advertisements generate. Henceforth, the research is conducted on London Olympics a mega sports event to understand the advertising effectiveness. Event marketing (advertisements) thus links a company’s brand to an activity for the purpose for creating experiences for attendees and promoting brand or product/service. The focus relies on what advertising effect the consumers have and how information is conveyed to consumers.